IMPLEMENTASI MODEL RME (REALISTIC MATHEMATICS EDUCATION) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM KONSEP KELILING DAN LUAS BANGUN DATAR DI KELAS IV SDN NGEMBE 1 - Septiana, Nanda (Universitas Islam Raden Rahmat Malang, 2023)
Students' understanding in following the learning process is not yet optimal so that student learning outcomes are below the KKM. The aim of this research is to improve mathematics learning outcomes on the concepts of perimeter and area of flat shapes using the Realistic Mathematics Education (RME) learning model for fourth grade students at SDN Ngembe 1 Pasuruan district. This research uses the PTK method with two cycles of action. Each cycle consists of planning, implementation, observation and reflection. Data processing is obtained from observation, documentation and student competency tests. The results of the research describe that student learning outcomes have improved in each cycle 1 and cycle 2. The final results of the research show that student learning outcomes in mathematics learning which discusses squares, rectangles and triangles are better using the RME (Realistic Mathematics Education) learning model. . Of the 28 students, in cycle 1 the average score of students in class reached 76.43 with 22 students completing (71.43%), and in cycle 2 it increased with the average score of students in class reaching 77.75 with complete 28 students (100%). In this case it can be concluded that students better understand mathematical concepts in real world contexts, increase student involvement and creativity in learning, and develop students' analytical skills, so that learning that is oriented towards student learning outcomes in class IV at SDN Ngembe 1 increases.